Size effects on the magnetic properties of Cu-Nb nanofilamentary wires processed by severe plastic deformation - Sandim, M.J.R.; Stamopoulos, D.; Sandim, H.R.Z.; Ghivelder, L.; Thilly, L.; Vidal, V.; Lecouturier, F.; Raabe, D. (SUPERCONDUCTOR SCIENCE & TECHNOLOGY, 2006)
We report on the influence of the microstructure on the AC and DC magnetic properties of Cu-3.5% Nb nanofilamentary wires. Samples obtained from a single Cu-3.5% Nb wire were subsequently submitted to different plastic strain levels via drawing so that their microstructure was altered. Noticeable differences are observed in their isothermal DC magnetization curves that present a double-peak structure. The first peak, which occurs at low magnetic fields, is attributed to superconductivity induced in the Cu matrix due to the proximity effect. It is argued that the second peak is related exclusively to niobium. The dependence of these two distinct peaks on the characteristic nanometre length scales of the samples, i.e. dimension of the Nb filaments and interfilamentary spacing, are discussed.